Ethnic inequality in retirement income: a comparative analysis of immigrant-native gaps in Western Europe - Jan Paul Heisig; Bram Lancee; Jonas Radl (Ageing & Society, 2018)
Previous research unequivocally shows that immigrants are less successful in the labour market than the native-born population. However, little is known about whether ethnic inequality persists after retirement. We use data on 16 Western European countries from the European Union Statistics on Income and Living Conditions (EU-SILC, 2004–2013) to provide the first comparative study of ethnic inequalities among the population aged 65 and older. We focus on the retirement income gap (RIG) between immigrants from non-European Union countries and relate its magnitude to country differences in welfare state arrangements. Ethnic inequality after retirement is substantial: after adjusting for key characteristics including age, education and occupational status, the average immigrant penalty across the 16 countries is 28 per cent for men and 29 per cent for women. Country-level regressions show that income gaps are smaller in countries where the pension system is more redistributive. We also find that easy access to long-term residence is associated with larger RIGs, at least for men. There is no clear evidence that immigrants' access to social security programmes, welfare state transfers to working-age households or the strictness of employment protection legislation affect the size of the RIG
Additional information: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer (DFG-geförderten) Allianz- bzw. Nationallizenz frei zugänglich / This publication is with permission of the rights owner freely accessible due to an Alliance licence and a national licence (funded by the DFG, German Research Foundation) respectively.
Keywords: 330; immigration; ethnic inequality; retirement income; pension systems; Europe; comparative research; welfare state; European Union Statistics on Income and Living Conditions (EU-SILC)